2015
DOI: 10.1039/c5dt00200a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation of cyclic peroxides by titanium and antimony chlorides

Abstract: First responders face extraordinary risks when dealing with organic peroxides such as TATP due to the extreme sensitivity of this class of explosives, and to a lack of a robust chemical means of safe and rapid neutralisation. The Lewis acids TiCl4 and SbCl3 have been found to demonstrate a novel degradation mechanism, with TiCl4 degrading a model cyclic peroxide in minutes when used in a two-fold excess, or ∼3 hours at half equivalence. The products cannot re-form peroxide compounds as is the case with acid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The experiments showed that SbCl 3 exhibits similar reactivity to TiCl 4 , although at a slower rate. In the article also a mechanism is proposed, consistent with the observations for both stoichiometric and sub-stoichiometric quantities of TiCl 4 [28].…”
Section: Decomposition and Other Reactionssupporting
confidence: 73%
See 1 more Smart Citation
“…The experiments showed that SbCl 3 exhibits similar reactivity to TiCl 4 , although at a slower rate. In the article also a mechanism is proposed, consistent with the observations for both stoichiometric and sub-stoichiometric quantities of TiCl 4 [28].…”
Section: Decomposition and Other Reactionssupporting
confidence: 73%
“…Pioneers of the field faced extraordinary risks when dealing with organic peroxides such as TATP due to the extreme sensitivity of this class of explosives, and to a lack of a robust chemical means of safe and rapid neutralization. Bali et al, studied degradation reactions of some peroxide compounds [28]. The Lewis acids TiCl 4 and SbCl 3 have been found to demonstrate a novel degradation mechanism.…”
Section: Decomposition and Other Reactionsmentioning
confidence: 99%
“…Due to slow decomposition they should be used immediately and not stored in the laboratory. Remains should be disposed of using an appropriate procedure …”
Section: Methodsmentioning
confidence: 99%